Strategi Pemberdayaan Berbasis Potensi Ekonomi Lokal di Desa Banjaranyar Kabupaten Ciamis Jawa Barat - Ana Melani; Tommi Hidayat; Aldi Ismail Fahmi (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2022)
In order to respond to problems in the village and enable the management of current resources in the village become more effective, development and empowerment techniques that focus on rural communities are needed. As was done by the residents of Banjarayar Village, who initiated by reading out about option to start honey bees as part of their economic development operations. Then, as this prospect grew in popularity, many local residents demanded that it be turned into a process, and the society agreed to create a site in the format of groups. The group acts as a conduit for gaining access to the required network. It's fascinating to watch how the community takes the initiative on its own to handle the potential in the form of natural resources. It's remarkable to observe how the community has taken the initiative to handle the potential they have in terms of natural resources and human resource management through honey bee agriculture activities. Data was collected through interviews, discussion forums, and observation as part of the qualitative research process. The data was collected between September 2020 and February 2021. The community's understanding of the group's goals to encourage participation from individual to joint participation, the existence of an understanding to make the entire commodity, honey, create innovation in the form of derivative products, and the understanding of each participant to help expand other stakeholders, including government agencies, academics, and the private sector, to strengthen the group.